Hydrogen: A Potential New Adjuvant Therapy for COVID-19 Patients - Yang, Fuxun; Yue, Ruiming; Luo, Xiaoxiu; Liu, Rongan; Huang, Xiaobo (Frontiers in Pharmacology, 2020)
Hydrogen has been shown to have antioxidant, anti-inflammatory, hormone-regulating, and apoptosis-resistance properties, among others. Based on a review of the research, the use hydrogen might reduce the destructive cytokine storm and lung injury caused by SARS-CoV-2 during COVID-19 (Corona Virus Disease 2019) in the early stage, stimulating ropy sputum drainage, and ultimately reducing the incidence of severe disease. Molecular hydrogen treatment has potential to become a new adjuvant therapy for COVID-19, but its efficacy and safety require large clinical trials and for further confirmation